Sprayed concrete with high crack resistance and low rebound rate and preparation method thereof
By using a combination of nano-aerogel, polypropylene fiber and modified vermiculite in sprayed concrete, the composite crosslinking network structure and self-repair effect are formed, and the problem of insufficient crack resistance and durability in the prior art is solved, and the problem of insufficient crack resistance and durability in the existing technology is achieved. High crack resistance and low rebound rate sprayed concrete significantly improves its service life in complex environments.
Patent Information
- Application Number
- CN202411234387.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-07
AI Technical Summary
The existing spray concrete preparation methods have shortcomings in improving crack resistance and durability, and have failed to meet the needs of low rebound rate and high crack resistance at the same time.
The spray concrete is prepared by nano-aerogel, polypropylene fiber and modified vermiculite. The water dispersion loss rate is reduced through the water-retaining and hygroscopic properties of nano-aerogels. The high fracture strength and elastic modulus of polypropylene fiber form a composite with the modified vermiculite. The cross-linked network structure improves crack resistance and enhances durability through the self-healing effect of the modification liquid.
It significantly improves the crack resistance and durability of sprayed concrete, reduces the rebound rate, extends the service life of the tunnel structure, and meets the high performance requirements of tunnel lining in complex environments.
Smart Images

Figure CN119263722A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete preparation, and in particular to a shotcrete with high crack resistance and low rebound rate and a preparation method thereof. Background Art
[0002] Shotcrete is widely used in railway, highway, water conservancy, mining and other industries. Shotcrete uses air pressure to spray high-slump concrete at high speed onto the sprayed surface, instantly forming a permanent lining concrete. High-performance shotcrete needs to have good pumpability and sprayability, high strength and excellent durability. Good sprayability is the key to reducing the rebound rate of concrete and increasing the thickness of a single spray, while high strength and durability are to ensure its protective effect on the deformation of tunnel surrounding rocks in complex environments and to improve its structural service life. Shotcrete is composed of cement, mineral admixtures, admixtures, water, etc. It has special requirements for water-cement ratio, amount of cementitious materials, sand ratio, etc. The working performance and durability of shotcrete obtained by different compositions, proportions and preparation methods vary greatly. Therefore, it is very important to select the composition, proportion and preparation method of shotcrete.
[0003] The shotcrete disclosed in patent document CN 117886575 mainly improves its strength and reduces its rebound rate by adding modified additives and functional agents; while the shotcrete preparation method disclosed in patent document CN 118084437 improves the dispersion effect of steel fibers and reduces its rebound rate by modifying the accelerating agent. However, the defects of the shotcrete preparation method in the prior art are that, on the one hand, only the low rebound rate and high strength of the shotcrete are considered, but its crack resistance is not considered; on the other hand, the crack resistance of the shotcrete is considered, but its durability is not involved.
[0004] Therefore, seeking a new method for preparing shotcrete to solve the above-mentioned defects is a problem that needs to be solved urgently. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a high crack resistance, low rebound rate shotcrete and its preparation method. The present invention creatively uses nano aerogel, polypropylene fiber, and modified vermiculite to prepare shotcrete, and uses the water retention and moisture absorption characteristics of nano aerogel to play an internal curing role inside the concrete, thereby reducing the internal water loss rate and weakening the shrinkage of concrete. At the same time, the composite cross-linked network structure formed by the high breaking strength and elastic modulus of polypropylene crude fiber and modified vermiculite can greatly improve the crack resistance and durability of shotcrete under the interaction; further, when the concrete cracks, the modified vermiculite, the modified liquid flows out from the internal cavity of the vermiculite, adheres to and solidifies at the crack to achieve a self-repairing effect, thereby better limiting the deformation of the tunnel structure and improving the service life of the tunnel lining in a complex environment.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A shotcrete with high crack resistance and low rebound rate is composed of the following raw materials in parts by weight: 420-450 parts of ordinary Portland cement, 10-60 parts of nano aerogel, 850-950 parts of coarse aggregate, 700-800 parts of fine aggregate, 5-35 parts of polypropylene fiber, 5-15 parts of water reducer, 3-5 parts of cellulose, 170-190 parts of water and 300-400 parts of modified vermiculite.
[0008] Preferably, the modified vermiculite is prepared by the following method:
[0009] S11. Acid hydrolysis: 500-600 parts by mass of vermiculite were immersed in a hydrochloric acid solution having a concentration of 1-3 mol / L for 1-2 h;
[0010] S12 Calcination: The vermiculite treated in step S11 is heated to 400-500 ℃, kept for 1-2h and then taken out to obtain expanded vermiculite;
[0011] S13. Vermiculite modification: 300-400 parts by mass of expanded vermiculite are immersed in the modification liquid, and vacuumized at the same time, and then taken out after standing for 1-2 hours to obtain modified vermiculite.
[0012] Preferably, the modified liquid comprises the following components in parts by mass: 100-200 parts of sodium trithiocarbonate, 300-400 parts of water, 80-100 parts of phenolic resin, 80-100 parts of cyclohexanedimethanol divinyl ether, 10-20 parts of azobisisobutyronitrile, and 15-30 parts of 3-glycidylpropyltrimethoxysilane.
[0013] Preferably, in step S13, the working parameters of the vacuum treatment are: vacuum degree 0.5-2Pa.
[0014] Preferably, the strength grade of the ordinary Portland cement is greater than or equal to 42.5; and the water reducer is a polycarboxylate water reducer.
[0015] Preferably, the nano aerogel is a spherical particle with a particle size of 100-300 nm.
[0016] Preferably, the polypropylene fiber has a diameter of 100-400 μm and an elastic modulus of 4000-7000 MPa.
[0017] Preferably, the fine aggregate is artificial sand with a fineness modulus ranging from 2.5 to 2.8; the coarse aggregate is gravel with a particle size ranging from 5 to 10 mm.
[0018] Preferably, the cellulose is selected from one or more of carboxymethyl cellulose and hydroxypropyl cellulose; the viscosity of the cellulose is 50,000-100,000.
[0019] A method for preparing shotcrete with high crack resistance and low rebound rate, which is used to prepare the shotcrete, comprises the following steps:
[0020] S1. Ordinary Portland cement, nano aerogel, coarse aggregate, fine aggregate, polypropylene fiber, cellulose, and modified vermiculite were weighed according to the set ratio, and then poured into a mixer and dry mixed for 60-90s;
[0021] S2. Then weigh the corresponding proportion of water reducer and water, mix them evenly, add them into a mixer and stir them evenly to obtain the shotcrete with high crack resistance and low rebound rate.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention utilizes low-viscosity cellulose to improve the bonding strength of shotcrete, thereby reducing the rebound rate of shotcrete;
[0024] 2. The present invention creatively uses nano aerogel, polypropylene fiber, and modified vermiculite to prepare shotcrete. The nano aerogel has the characteristics of water retention and moisture absorption, and plays an internal curing role inside the concrete, thereby reducing the internal water loss rate and weakening the shrinkage of the concrete. At the same time, the polypropylene crude fiber has high fracture strength and elastic modulus and forms a composite cross-linked network structure with the modified vermiculite. Under the interaction, the crack resistance and durability of the shotcrete can be greatly improved; further, when the concrete cracks, the modified vermiculite, the modified liquid flows out from the internal cavity of the vermiculite, adheres to and solidifies at the crack to achieve a self-repairing effect, thereby better limiting the deformation of the tunnel structure and improving the service life of the tunnel lining in a complex environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1This is a process flow chart of the preparation of the shotcrete with high crack resistance and low rebound rate according to the present invention;
[0026] Figure 2 The present invention is a flow chart of the preparation process of the modified vermiculite;
[0027] Figure 3 The stress-strain curve of the shotcrete with high crack resistance and low rebound rate prepared in Example 1 of the present invention;
[0028] Figure 4 This is a stress-strain curve of the shotcrete prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0029] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] See also Figure 1-4 , the present invention provides a technical solution:
[0031] Example 1
[0032] A method for preparing shotcrete with high crack resistance and low rebound rate:
[0033] S1. Ordinary Portland cement, nano aerogel, coarse aggregate, fine aggregate, polypropylene fiber, cellulose, and modified vermiculite were weighed according to the set ratio, and then poured into a mixer and dry mixed for 60s;
[0034] S2. Then weigh the corresponding proportion of water reducer and water, mix them evenly, add them into a mixer and stir them evenly to obtain the shotcrete with high crack resistance and low rebound rate.
[0035] In the above process, the amount of each raw material is as follows:
[0036] Components Dosage(kg) Ordinary Portland Cement 4.2 Nano aerogel 1 Coarse aggregate (stone) 85 Fine aggregate (artificial sand) 70 Polypropylene fiber 3.5 Cellulose (Carboxymethyl Cellulose) 0.5 Modified Vermiculite 30 Water reducing agent (polycarboxylate water reducing agent) 1 water 17
[0037] In the above process, the strength grade of the ordinary Portland cement is greater than or equal to grade 42.5;
[0038] The nano aerogel is a spherical particle with a particle size of 100 nm;
[0039] The polypropylene fiber has a diameter of 100 μm and an elastic modulus of 4000 MPa;
[0040] The fineness modulus of the fine aggregate is in the range of 2.5-2.8;
[0041] The particle size of the coarse aggregate is in the range of 5-10 mm;
[0042] The viscosity of the cellulose is 50,000;
[0043] In the above process, the modified vermiculite is prepared by the following method:
[0044] S11. Acid hydrolysis: 50 kg of vermiculite was immersed in a 1 mol / L hydrochloric acid solution for 1.5 h;
[0045] S12 Calcination: The vermiculite treated in step S11 was heated to 500 ℃, kept for 1h and then taken out to obtain expanded vermiculite;
[0046] S13. Vermiculite modification: 30 kg of expanded vermiculite was immersed in the modification liquid and vacuumed to 0.5 Pa at the same time. After standing for 1 hour, the modified vermiculite was taken out to obtain the modified vermiculite.
[0047] In the above process, the modified liquid is prepared by mixing 10 kg sodium trithiocarbonate, 30 kg water, 8 kg phenolic resin, 8 kg cyclohexanedimethanol divinyl ether, 1 kg azobisisobutyronitrile, and 1.5 kg 3-glycidylpropyltrimethoxysilane.
[0048] The phenolic resin is phenol formaldehyde resin with the brand name HRJ12952, purchased from SI Group International.
[0049] Example 2
[0050] A method for preparing shotcrete with high crack resistance and low rebound rate:
[0051] S1. Ordinary Portland cement, nano aerogel, coarse aggregate, fine aggregate, polypropylene fiber, cellulose, and modified vermiculite were weighed according to the set ratio, and then poured into a mixer and dry mixed for 90s;
[0052] S2. Then weigh the corresponding proportion of water reducer and water, mix them evenly, add them into a mixer and stir them evenly to obtain the shotcrete with high crack resistance and low rebound rate.
[0053] In the above process, the amount of each raw material is as follows:
[0054]
[0055]
[0056] In the above process, the strength grade of the ordinary Portland cement is greater than or equal to grade 42.5;
[0057] The nano aerogel is a spherical particle with a particle size of 200 nm;
[0058] The polypropylene fiber has a diameter of 400 μm and an elastic modulus of 7000 MPa;
[0059] The fineness modulus of the fine aggregate is in the range of 2.5-2.8;
[0060] The particle size of the coarse aggregate is in the range of 5-10 mm;
[0061] The viscosity of the cellulose is 100,000;
[0062] In the above process, the modified vermiculite is prepared by the following method:
[0063] S11. Acid hydrolysis: immerse 60 kg of vermiculite in a 3 mol / L hydrochloric acid solution for 1 h;
[0064] S12 Calcination: The vermiculite treated in step S11 was heated to 450 ° C, kept warm for 1.5h and then removed to obtain expanded vermiculite;
[0065] S13. Vermiculite modification: 40 kg of expanded vermiculite was immersed in the modification liquid and vacuumed to 0.5 Pa at the same time. After standing for 2 hours, the modified vermiculite was taken out to obtain the modified vermiculite.
[0066] In the above process, the modified liquid is prepared by mixing 20 kg sodium trithiocarbonate, 40 kg water, 8 kg phenolic resin, 10 kg cyclohexanedimethanol divinyl ether, 2 kg azobisisobutyronitrile, and 2 kg 3-glycidylpropyltrimethoxysilane.
[0067] The phenolic resin is phenol formaldehyde resin with the brand name HRJ12952, purchased from SI Group International.
[0068] Example 3
[0069] A method for preparing shotcrete with high crack resistance and low rebound rate:
[0070] S1. Ordinary Portland cement, nano aerogel, coarse aggregate, fine aggregate, polypropylene fiber, cellulose, and modified vermiculite were weighed according to the set ratio, and then poured into a mixer and dry mixed for 90s;
[0071] S2. Then weigh the corresponding proportion of water reducer and water, mix them evenly, add them into a mixer and stir them evenly to obtain the shotcrete with high crack resistance and low rebound rate.
[0072] In the above process, the amount of each raw material is as follows:
[0073] Components Dosage(kg) Ordinary Portland Cement 4.3 Nano aerogel 5 Coarse aggregate (stone) 90 Fine aggregate (artificial sand) 75 Polypropylene fiber 1 Cellulose (Carboxypropylcellulose) 0.4 Modified Vermiculite 35 Water reducing agent (polycarboxylate water reducing agent) 1.5 water 18
[0074] In the above process, the strength grade of the ordinary Portland cement is greater than or equal to grade 42.5;
[0075] The nano aerogel is a spherical particle with a particle size of 200 nm;
[0076] The polypropylene fiber has a diameter of 400 μm and an elastic modulus of 7000 MPa;
[0077] The fineness modulus of the fine aggregate is in the range of 2.5-2.8;
[0078] The particle size of the coarse aggregate is in the range of 5-10 mm;
[0079] The viscosity of the cellulose is 100,000;
[0080] In the above process, the modified vermiculite is prepared by the following method:
[0081] S11. Acid hydrolysis: 60 kg of vermiculite was immersed in a 1.5 mol / L hydrochloric acid solution for 1.25 h;
[0082] S12 Calcination: The vermiculite treated in step S11 was heated to 400 ℃, kept for 2h and then taken out to obtain expanded vermiculite;
[0083] S13. Vermiculite modification: 35 kg of expanded vermiculite was immersed in the modification liquid and vacuumed to 2 Pa at the same time. After standing for 2 hours, the modified vermiculite was taken out to obtain the modified vermiculite.
[0084] In the above process, the modified liquid is prepared by mixing 15 kg sodium trithiocarbonate, 35 kg water, 9 kg phenolic resin, 9 kg cyclohexanedimethanol divinyl ether, 2 kg azobisisobutyronitrile, and 2.5 kg 3-glycidylpropyltrimethoxysilane.
[0085] The phenolic resin is phenol formaldehyde resin with the brand name HRJ12952, purchased from SI Group International.
[0086] Comparative Example
[0087] Comparative Example 1: Comparative Example 1 is different from Example 1 in that the raw material components for preparing shotcrete described in Example 1 are partially omitted in Comparative Example 1, thereby omitting the use of nano aerogel, and the remaining steps are exactly the same in Comparative Example 1 and Example 1.
[0088] Comparative Example 2: Comparative Example 2 is different from Example 1 in that the raw material components for preparing shotcrete described in Example 1 are partially omitted in Comparative Example 2, thereby omitting the use of nano aerogel and polypropylene fiber, and the remaining steps are exactly the same in Comparative Example 2 and Example 1.
[0089] Comparative Example 3: Comparative Example 3 is different from Example 1 in that, in Comparative Example 3, some of the raw material components for preparing shotcrete described in Example 1 are omitted, thereby omitting the use of modified vermiculite, and the remaining steps are exactly the same in Comparative Example 3 and Example 1.
[0090] Comparative Example 4: Comparative Example 4 is different from Example 1 in that, in Comparative Example 4, some of the raw material components for preparing shotcrete described in Example 1 are omitted, thereby omitting the use of nano aerogel, polypropylene fiber, and modified vermiculite, and the remaining steps are exactly the same in Comparative Example 4 and Example 1.
[0091] According to the experimental requirements of GB 50204-2015, GB / T 50081-2019, GB / T 50082-2009, GB / T50081-2002, and JGJ / T 23-2011, the compressive strength, bending resistance, elastic modulus, and rebound rate of the shotcrete prepared in Examples 1-3 and Comparative Examples 1-4 were tested, and the test results are shown in Table 1:
[0092] Table 1. Test results of compressive strength, bending resistance, elastic modulus and rebound rate of shotcrete prepared in Examples 1-3 and Comparative Examples 1-4
[0093]
[0094] Referring to the above content, it can be seen that the present invention provides a high crack resistance, low rebound rate shotcrete, the compressive strength is ≥58MPa, the highest can reach 63.1MPa; the flexural strength is ≥4.7MPa, the highest can reach 5.9MPa, and the concrete has no strength shrinkage phenomenon in long-term use, and its performance is far better than ordinary concrete, meets the technical requirements of shotcrete, and also meets the high performance requirements of tunnel engineering for concrete; secondly, the elastic modulus is higher than 35GPa, and the rebound rate is lower than 9.1%, indicating that the shotcrete prepared in this application is a high crack resistance, low rebound rate and excellent performance concrete;
[0095] At the same time, as shown in Table 1 and Figure 3 , Figure 4As shown, the significant difference in performance between Examples 1-3 of the present application and Comparative Examples 1-4 further proves that the present invention utilizes the water-retaining and moisture-absorbing properties of nano-aerogel to play an internal curing role inside the concrete, thereby reducing the internal water loss rate and weakening the shrinkage of the concrete. At the same time, the composite cross-linked network structure formed by the polypropylene crude fiber having high fracture strength and elastic modulus and the modified vermiculite can greatly improve the crack resistance and durability of the shotcrete under the interaction; and further, when the modified vermiculite cracks in the concrete, the modified liquid flows out from the internal cavity of the vermiculite, adheres to and solidifies at the crack to achieve a self-repairing effect, thereby better limiting the deformation of the tunnel structure and improving the service life of the tunnel lining under complex environments.
[0096] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A shotcrete with high crack resistance and low rebound rate, characterized in that: The invention is composed of the following raw materials in parts by weight: 420-450 parts of ordinary Portland cement, 10-60 parts of nano aerogel, 850-950 parts of coarse aggregate, 700-800 parts of fine aggregate, 5-35 parts of polypropylene fiber, 5-15 parts of water reducer, 3-5 parts of cellulose, 170-190 parts of water and 300-400 parts of modified vermiculite.
2. The high crack resistance and low rebound rate shotcrete according to claim 1, characterized in that: The modified vermiculite is prepared by the following method: S11. Acid hydrolysis: 500-600 parts by mass of vermiculite were immersed in a hydrochloric acid solution having a concentration of 1-3 mol / L for 1-2 h; S12 Calcination: The vermiculite treated in step S11 is heated to 400-500 ℃, kept for 1-2h and then taken out to obtain expanded vermiculite; S13. Vermiculite modification: 300-400 parts by mass of expanded vermiculite are immersed in the modification liquid, and vacuumized at the same time, and then taken out after standing for 1-2 hours to obtain modified vermiculite.
3. The high crack resistance and low rebound rate shotcrete according to claim 2, characterized in that: The modified liquid comprises the following components by mass: 100-200 parts of sodium trithiocarbonate, 300-400 parts of water, 80-100 parts of phenolic resin, 80-100 parts of cyclohexanedimethanol divinyl ether, 10-20 parts of azobisisobutyronitrile, and 15-30 parts of 3-glycidylpropyltrimethoxysilane.
4. The high crack resistance and low rebound rate shotcrete according to claim 2, characterized in that: In step S13, the working parameters of the vacuum treatment are: vacuum degree 0.5-2Pa.
5. The high crack resistance and low rebound rate shotcrete according to claim 1, characterized in that: The strength grade of the ordinary Portland cement is greater than or equal to 42.5; and the water reducer is a polycarboxylate water reducer.
6. The high crack resistance and low rebound rate shotcrete according to claim 1, characterized in that: The nano aerogel is a spherical particle with a particle size of 100-300nm.
7. The high crack resistance and low rebound rate shotcrete according to claim 1, characterized in that: The polypropylene fiber has a diameter of 100-400 μm and an elastic modulus of 4000-7000 MPa.
8. The high crack resistance and low rebound rate shotcrete according to claim 1, characterized in that: The fine aggregate is artificial sand with a fineness modulus ranging from 2.5 to 2.8; the coarse aggregate is gravel with a particle size ranging from 5 to 10 mm.
9. The high crack resistance and low rebound rate shotcrete according to claim 1, characterized in that: The cellulose is selected from one or more of carboxymethyl cellulose and hydroxypropyl cellulose; the viscosity of the cellulose is 50,000-100,000.
10. A method for preparing shotcrete with high crack resistance and low rebound rate, used for preparing the shotcrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Ordinary Portland cement, nano aerogel, coarse aggregate, fine aggregate, polypropylene fiber, cellulose, and modified vermiculite were weighed according to the set ratio, and then poured into a mixer and dry mixed for 60-90s; S2. Then weigh the corresponding proportion of water reducer and water, mix them evenly, add them into a mixer and stir them evenly to obtain the shotcrete with high crack resistance and low rebound rate.
Citation Information
Cited By
High-performance sprayed concrete and preparation method thereof
CN120136493A
A hierarchical water-retaining type concrete pulp raising agent, a preparation method and application thereof
CN122771648A